Vital signs: Valid indicators to assess pain in intensive care unit patients? An observational, descriptive study. (20th July 2018) - Erden, Sevilay; Demir, Nevra; Ugras, Gulay A.; Arslan, Umut; Arslan, Sevban
Abstract: Pain is a stressor for intensive care unit (ICU) patients, and inadequate pain assessment has been linked to increased morbidity and mortality. One hundred and twenty patients were evaluated during three periods: (T1) 1 min before, (T2) during, and (T3) 20 min after the nociceptive procedure. For each patient, data were obtained through at least two nociceptive procedures. Conscious patients' self‐reports of pain were assessed using the Numerical Rating Scale and Visual Analog Scale. For unconscious patients, the Behavioral Pain Scale was used instead. Descriptive statistical methods, Friedman's test, and Spearman's rank correlation coefficient were used for the data analysis. Significant changes were observed in heart rate (HR), respiratory rate (RR), and peripheral oxygen saturation (SpO2 ) during nociceptive procedures. The HR, RR, and pain scores increased, while the SpO2 decreased. Positive correlation coefficients were observed between the pain intensity and HR and RR levels. According to our study findings, vital signs are not strong indicators for pain assessment in neurosurgery ICU patients. However, HR and RR can be used as cues when behavioral indicators are not valid in these unconscious patients.